The level of work engagement at Generation Z - Suhaini Suhaini; Reny Yuniasanti (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTGeneration Z is a generation whose numbers dominate and some have entered the workforce so that it will be a new challenge for human resource management. The reason of this consider is to decide the level of work engagement in era Z. The subjects in this ponder measured to 100 era Z representatives. The subjects in this think about summed to 100 era Z workers. The examining procedure utilized was comfort inspecting. The inquire about strategy utilized is clear quantitative investigate strategy. Information collection in this think about utilized a work engagement scale that was orchestrated based on five viewpoints, to be specific vigor, devotion, retention. Expressive information examination strategies utilize comparison of theoretical cruel and observational cruel and test contrasts with OneWay ANOVA. The results showed work engagement in generation Z was in the high category.ABSTRACTGenerasi Z merupakan generasi yang jumlahnya mendominasi dan sebagian telah memasuki dunia kerja sehingga akan menjadi tantangan baru bagi manajemen sumber daya manusia. Tujuan dilakukan riset berikut adalah guna mengetahui tingkatan work engagement pada generasi Z. Subjek pada riset ini jumlahnya 100 orang karyawan generasi Z. Teknik sampling yang digunakan adalah convenience sampling. Metode riset yang digunakan yaitu metode studi kuantitatif deskriptif. Pengumpulan data pada riset ini menggunakan skala work engagement yang dirancang sesuai lima aspek yaitu vigor, dedication, absorption. Teknik analisis data deskriptif menggunakan perbandingan mean hipotetik dan mean empirik serta pengujian perbedaan dengan One-Way ANOVA. Hasil riset memaparkan work engagement pada generasi Z ada dalam kategori tinggi